2010
DOI: 10.1158/0008-5472.can-09-3141
|View full text |Cite
|
Sign up to set email alerts
|

LYN Is a Mediator of Epithelial-Mesenchymal Transition and a Target of Dasatinib in Breast Cancer

Abstract: Epithelial-mesenchymal transition (EMT), a switch of polarized epithelial cells to a migratory, fibroblastoid phenotype, is considered a key process driving tumor cell invasiveness and metastasis. Using breast cancer cell lines as a model system, we sought to discover gene expression signatures of EMT with clinical and mechanistic relevance. A supervised comparison of epithelial and mesenchymal breast cancer lines defined a 200-gene EMT signature that was prognostic across multiple breast cancer cohorts. The i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 48 publications
9
124
1
4
Order By: Relevance
“…Expression of both the wild-type and S768F mutant allele of endoplasmic reticulum to nucleus signalling 1 (ERN1, also IRE1) are the second and fourth most frequently recovered transposon cDNAs in our study (Table 2), corroborating recent description of ERN1 as playing key roles in tumour angiogenesis, growth and invasion [26,27]. In contrast, for the v-yes-1 Yamaguchi sarcoma viral related oncogene homologue (LYN) kinase that is implicated in a wide variety of cancers [28][29][30], while expression of the wild-type kinase is the third most frequent occurrence, we never recovered any tumours expressing the D385Y mutant ( Table 2). This would suggest that the D385Y mutation is potentially a loss-of-function mutation, though this has to be characterised molecularly with biochemical and cellbased activity assays.…”
Section: Validating Cancer Mutations By Tumourigenesis In Vivosupporting
confidence: 89%
“…Expression of both the wild-type and S768F mutant allele of endoplasmic reticulum to nucleus signalling 1 (ERN1, also IRE1) are the second and fourth most frequently recovered transposon cDNAs in our study (Table 2), corroborating recent description of ERN1 as playing key roles in tumour angiogenesis, growth and invasion [26,27]. In contrast, for the v-yes-1 Yamaguchi sarcoma viral related oncogene homologue (LYN) kinase that is implicated in a wide variety of cancers [28][29][30], while expression of the wild-type kinase is the third most frequent occurrence, we never recovered any tumours expressing the D385Y mutant ( Table 2). This would suggest that the D385Y mutation is potentially a loss-of-function mutation, though this has to be characterised molecularly with biochemical and cellbased activity assays.…”
Section: Validating Cancer Mutations By Tumourigenesis In Vivosupporting
confidence: 89%
“…Dasatinib reduced migration and invasion in head and neck squamous cell carcinoma, non-small cell lung cancer [29] and in breast cancer cell lines [30,31]. Interestingly, basal-like/triplenegative breast cancer cell lines with high levels of caveolin-1 expression, like MDA-MB-231 cells, are characterized by sensitivity to Dasatinib, while low expression of caveolin-1 correlates with resistance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lyn has been described as an important target in haematopoietic and solid tumors including TNBC, and was proven to be one of the most overexpressed kinase in TNBC cell lines. 29,33 Lyn plays an important role in the migration of cancer cells and was shown that can interact with p130Cas, one of the member of the focal adhesion complex. 34 Association of p130Cas with motility, invasion and survival of TNBC cells has been shown before by several publications.…”
Section: Discussionmentioning
confidence: 99%
“…33 Based on these result we selected Lyn to analyze its function on the migration and viability of MDA-MB-231, Hs578T and BT549 cells. It is known that Lyn interacts 34 with one of the members of the focal adhesion complex, namely p130Cas.…”
Section: Lyn and P130cas Affect The Migration Of Triple Negative Breamentioning
confidence: 99%